A Multi-Institutional Study Investigating the Teaching and Learning of Organic Chemistry - Streja, Nicholas Stephan (Université d'Ottawa / University of Ottawa, 2023)
Undergraduate students are completing organic chemistry courses without gaining a firm comprehension of the material (T. L. Anderson & Bodner, 2008; Bhattacharyya & Bodner, 2005, 2014). Traditional organic chemistry curricula have critical drawbacks for students' learning (Cooper & Stowe, 2018; Flynn & Ogilvie, 2015; Stowe & Cooper, 2017). New curricula have been proposed and implemented to address drawbacks but tools are needed to measure the different learning aspects of these curricula. Herein, I describe the development and implementation of two such educational measurement tools to assess different aspects of organic chemistry curricula. My research consisted of two main projects: 1) exploring undergraduate students' understanding of reactivity principles in organic chemistry by developing and implementing a questionnaire and 2) assessing students self-efficacy beliefs in organic chemistry by developing a quantitative survey. Through my projects we created measurement tools that can be used to assess different aspects of organic chemistry curricula. Both tools place heavy emphasis on reactivity principles in organic chemistry as the key to mastering the subject. Project 1: Exploring undergraduate students' understanding of reactivity principles in organic chemistry using the Organic Reactivity Questionnaire. A key skill in mastering organic chemistry is recognizing how different chemical concepts, like resonance or electronegativity, influence a reaction's outcome. Undergraduate students often struggle to apply reactivity principles to solve reaction mechanisms. Research has been done on how students interpret mechanistic arrows; however, less is known about how students interpret different chemical concepts when reasoning about reactivity. No measurement tools existed that explicitly examine how undergraduate students interpret different chemical concepts with respect to reactivity. Therefore, we developed an educational tool to measure how undergraduate organic chemistry students interpret chemical concepts and apply reactivity principles, called the Organic Reactivity Questionnaire (ORQ). We administered the ORQ to undergraduate students in Organic Chemistry I and Organic Chemistry II at universities across Canada. We recruited students from four different universities across three provinces to complete the ORQ online. We analyzed the data to identify themes related to how undergraduate students at the end of Organic Chemistry I interpret reactivity principles. Students' definitions of nucleophilicity and electrophilicity largely aligned with expectations. Students often used electronegativity in their explanations of reactivity even though it was never the most relevant factor for answering the questions. Students struggled to correctly reason using inductive effects and steric hindrance. Students were more successful in determining the direction of an acid-base equilibrium when given pKₐ values and would incorrectly associate charge with instability. Participants were largely successful in determining the better leaving group when atom size was the most relevant factor but would still often resort to using electronegativity. Findings from this study can help educators identify where students misinterpret chemical concepts and how educators can then adapt their teaching to address these misinterpretations. From these results, we have identified potential modifications for future implementations of the ORQ such that it could be used as a formative assessment and research tool. Project 2: Developing the Self-Efficacy Beliefs in Organic Chemistry survey to assess undergraduate students' self-efficacy beliefs in organic chemistry. Self-efficacy beliefs are an individual's beliefs in their ability to succeed at a given task or obtain a certain goal (Bandura, 1977, 2006). Self-efficacy beliefs are correlated with students' achievement in various STEM fields, where students with high self-efficacy in a certain discipline often perform well (Flaherty, 2020). In contrast, low self-efficacy beliefs are associated with high attrition rates and lower student success in STEM courses (Chen, 2014). Organic chemistry has an infamous reputation for being a difficult, content heavy course with high attrition rates (Chen, 2014; Gilstrap, 2020). Little is known about how self-efficacy beliefs in organic chemistry might be related to student success in organic chemistry courses. We developed the Self-Efficacy Beliefs in Organic Chemistry survey (SEBOC) to measure undergraduate students' self-efficacy beliefs in Organic Chemistry I and II. We aligned the SEBOC with the Patterns of Mechanisms curriculum at the University of Ottawa and focused its content on reactivity. This study focused on collecting validity and reliability evidence for use of the SEBOC in Organic Chemistry I. Validity is analogous to an instrument's accuracy and is a gauge of whether the instrument is measuring what it was intended to; reliability is analogous to an instrument's precision and gauges the consistency of the instrument's measurements. We collected validity evidence for face, test content, response process, and internal structure. Validity evidence checks the accuracy of the SEBOC and ensures that it measured what we intended it to. We consulted experts in the fields of organic chemistry, education, and chemistry education to collect validity evidence related to test content. We administered the SEBOC to students in Organic Chemistry I courses that followed a Patterns of Mechanisms curriculum and conducted an exploratory factor analysis to probe the internal structure of the SEBOC. Herein we propose a three-factor structure with 18 items to evaluate undergraduate students' self-efficacy beliefs in organic chemistry. All items possessed strong internal reliability with all Cronbach's α values ≥0.8. The results from the validity and reliability analysis suggest that the SEBOC could be used to accurately assess students' self-efficacy beliefs in introductory organic chemistry courses. Future work using the SEBOC will be to conduct a confirmatory analysis of the proposed model. A confirmatory analysis would provide greater evidence that the SEBOC generates valid data by testing the proposed factor model on the target population (i.e., OCII). Researchers could then use the SEBOC to assess and draw conclusions about the self-efficacy beliefs of the target population.
Keywords: Chemistry; Education; Curricula; Organic